Propuesta del diseño conceptual de un proceso para la pirólisis de biomasa por medio de simulación (2021)
The present project makes a proposal of conceptual design of a pyrolysis process from biomass, for its accomplishment a research divided in three phases is carried out, each one complementary and cumulative to give fulfillment to the development. At the beginning, bibliographic information was compiled to determine the state of the art of the thermochemical process under study, and also to search for kinetic models that were validated by the authors in order to relate the kinetics within the reactive process. The kinetic model proposed by Koufopanos was chosen, where from sawdust and at a temperature of 623 K products are obtained in gaseous phase (gases and volatiles) as well as in solid phase (char), thus giving way to the determination of the reactor to be used and in also the mathematical model that allowed to establish the equations that governed the behavior of this process as such.